CBDC and business cycle dynamics in a New Monetarist New Keynesian model - Katrin Assenmacher-Wesche; Lea Bitter; Annukka Ristiniemi (European Central Bank (ECB), 2023)
To study implications of an interest-bearing CBDC on the economy, we integrate a New Monetarist-type decentralised market that explicitly accounts for the means-of-exchange function of bank deposits and CBDC into a New Keynesian model with financial frictions. The central bank influences the store-of-value function of money through a conventional Taylor rule while it affects the means-of-exchange function of money through CBDC operations. Peak responses to monetary policy shocks remain similar in the presence of an interest-bearing CBDC, implying that monetary transmission is not impaired. At the same time however, the provision of CBDC helps smooth responses to macroeconomic shocks. By supplying CBDC, the central bank contributes to stabilising the liquidity premium, thereby affecting bank funding conditions and the opportunity costs of money, which dampens and smoothes the reaction of investment and consumption to macroeconomic shocks.
Keywords: E58; E41; E42; E51; E52; 330; Central bank digital currency; monetary policy; DSGE; search and matching